Nghiên cứu chế tạo gốm sứ hệ silic cacbua sử dụng làm phin lọc xỉ cho kim loại nóng chảy - Cương, Trần Văn; Xuân, Phan Thanh; Chinh, Trần Văn (Vietnam Journal of Chemistry, 2017)
Silicon carbide ceramic foam filter is a special technology. It has a foam porous structure of ceramic products, and its light weight, chemical stability, large surface area through-hole rate, corrosion resistance to molten metal erosion, high temperature, high strength, high pass rate, and good thermal shock resistance characteristics. It is mainly used in the field of metallurgy and casting metal liquid filtration and purification. Ceramic foam filters can be made of different pore size and porosity, in order to obtain satisfactory filtration effect. A process for producing a silicon carbide ceramic foam filter includes the steps of: preparing raw material becoming silicon carbide from a mixture of silicon carbide powder, alumina, zirconium silicate, talc and kaolin clay; adding the forming agents into the raw materials for silicon carbide generation, mixing the forming agents and the raw materials to obtain a raw material batch, shaping a foam structural body from the resulting mixture by extrusion, hydraulic press machine or mold for slip casting; drying the formed body, and sintering the formed body after drying. The structure and property of the silicon carbide ceramic foam filter were investigated by X-ray diffraction (XRD), Scanning Electronic Microscopy (SEM). Keywords. Silicon carbide ceramic, foam filter, molten metal.